Childhood borderline lepromatous leprosy - Martin Susanto; Grace Dumamawarni Hutahaean; Tiopan Napitupulu; Andre Marolop Pangihutan Siahaan (Indonesian Pediatric Society Publishing House, 2024)
Leprosy (Morbus Hansen) is a chronic, severe infectious disease caused by the Mycobacterium leprae that mostly affects the skin, mucosa, eyes, and nerves. Despite the availability of effective treatment, leprosy has become a major public health problem in many developing countries.